The role of economic information technology in the use of functional foods and herbaria and the development of microregional spaces - Kmeth, Sándor (Acta Agraria Debreceniensis, 2015)
This study aims to define the concept and significance of herbarium in space and time. It compares the basic ideas of traditional and modern paradigms paying special attention to medicine and nutrition. It examines the notion and role of functional foods in the light of paradigm changes, health preservation, and healing. Concerning the improvement of microregional areas, it evaluates the possible role of herbaria in creating social cohesion, community building, education, and economy improvement.